Effectiveness of Dhikr to Intensity of Pain during Active Phase in Mothers Getting Inducing Labour - Nurhidayatul Mualimah; Irma Nurbaeti; Puspita Palupi (Universitas Padjadjaran, 2020)
Women in labor process with induction are more painful than normal labor that need to applicate an intervention to reduce pain in stage I labor. The purpose of this study is to determine the effect of dhikr towards intensity of pain of labor during the active phase of the mother with labour induction. The study was conducted since May until June 2018 with one group quasi-experimental design. Pain score is measured before and after dhikr using Visual Analog Scale (VAS) every 30 minutes during the active phase of first stage. The mothers who met criteria recruited as the samples. Fifteen muslim mothers who had first labor induction, starting cervical dilatation in 4 cm, gynecoid pelvis and completed cervical dilatation to 10 cm. Statistic analysis performed by ANOVA Repeated Measure test at Î± = 0.05. The result of the statistical test shows that dhikr has moderate effect of 32.5% to decrease the average score of induction pain at the active phase of first stage (value-p=0.08) after controlled with confounding variables; age and parity. Dhikr had an effect on the decrease of VAS score after 30 minutes intervention (p-value = 0.016), but did not affect the measurement at the end of the first stage of labour (p-value = 0.651). Therefore, dhikr could be used to control pain of induced labor during active phase of first stage. Suggested has teached pregnant women since the third trimester and combined with the other intervention to reduce labour pain.